Quantitative analysis of ro-vibrational spectra of ethylene: Line strengths of the v12 and v3 bands of 12C2H2D2-cis - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Konova Yu. V. Yuliya Vladimirovna; Aslapovskaya Yu. S. Yuliya Sergeevna; Sydow Ch. Christian; Beryozkin K. B. Kirill Borisovich; Bauerecker S. Sigurd (2021, 2021)
Title screen